Recent Advances in the Roles of Autophagy and Autophagy Proteins in Host Cells During Toxoplasma gondii Infection and Potential Therapeutic Implications - Subauste, Carlos S. (Frontiers in Cell and Developmental Biology, 2021)
Toxoplasma gondii is an obligate intracellular protozoan that can cause encephalitis and retinitis in humans. The success of T. gondii as a pathogen depends in part on its ability to form an intracellular niche (parasitophorous vacuole) that allows protection from lysosomal degradation and parasite replication. The parasitophorous vacuole can be targeted by autophagy or by autophagosome-independent processes triggered by autophagy proteins. However, T. gondii has developed many strategies to preserve the integrity of the parasitophorous vacuole. Here, we review the interaction between T. gondii, autophagy and autophagy proteins and expand on recent advances in the field including the importance of autophagy in regulation of invasion of the brain and retina by the parasite. We discuss studies that have begun to explore the potential therapeutic applications of the knowledge gained thus far.